(untitled) (Biological Sciences - PJSIR, 2005)
Even though castor oil is inedible, it has for long been an article of commerce. This is in large measure due to the versatility of the oil. This review discusses the extraction of castor oil and its refining methods, while emphasis is placed on the review of the industrial applications of the oil. Since castor oil is not edible, it could be substituted in many industrial application areas where edible oils are used. An awareness of the various applications of the oil can be used to emphasize the need for an increase in its production as a vital raw material for the chemical industries.